How does institutional context shape work-related functionings for regular and self-employed workers? A contextualised application of the capability approach to Belgium, France and the Netherlands - Focacci, Chiara Natalie; Pichault, François (International journal of sociology and social policy, 2023)
PurposeAccording to Sen's theoretical framework of capability (1985), individuals reach their full potential once they have the freedom, intended as the set of functionings at their disposal, to do so. However, many critiques have been developed against the lack of embeddedness of the capability approach in social and political relations and structures. In this article, the authors investigate the influence of three institutional contexts (Belgium, the Netherlands and France) on the respective work-related functionings of self-employed and regular workers, with a focus on human capital investment and institutional support offered to them.Design/methodology/approachData from the European Working Conditions Survey (EWCS) are used to highlight similarities and differences in building work-related functionings for regular and self-employed workers. A regression analysis is provided at the country level.FindingsIn the three labour markets, the authors find that the building of work-related functionings is more successful for regular employees, especially as regards institutional support. Self-employed workers, on the other hand, need to rely on their individual capability as regards employment protection and human capital investment. However, the authors find interesting differences between the three institutional contexts. In both Belgium and France, self-employed workers are subject to higher instability in terms of changes in salary and hours worked, whereas atypical work is better positioned in the Dutch labour market. The Netherlands is also characterised by a less significant gap between regular and self-employed workers with respect to participation in training.Originality/valueIn this article, the authors contextualise Sen's (1985) theoretical framework by taking into account the institutional differences of labour markets. In particular, the authors provide a novel application of his capability approach to regular and self-employed workers in an economically relevant European area.